The effects of lipoprotein surface charge on cholesterol metabolism. - Stamler, Christopher John. (University of Ottawa (Canada), 2002)
To examine the role that lipoprotein surface charge plays in cholesterol metabolism in vivo, we characterized the effects of an intravenous injection of an uncharged phospholipid (phosphatidylcholine, PC (∼8 mg/kg)) or an anionic phospholipid (phosphatidylinositol, PI (∼9 mg/kg)) into fasted rabbits. The PI-injection significantly (P < 0.05) increased the negative surface charge of the lipoproteins. The clearance of tritiated-cholesterol from the PI-injected rabbit-plasma was ∼50% greater when compared to controls (P < 0.05). The PI-injection also prevented the formation of cholesteryl ester. To determine how increased lipoprotein PI content may regulate cholesterol clearance by the liver, cell culture studies using a human hepatoma cell-line were undertaken. In vitro enrichment of human plasma or high density lipoproteins with PI caused a ∼2 fold stimulation in cholesterol cellular uptake, relative to controls. PI-enrichment did not affect cellular cholesterol-uptake from low density lipoproteins. These results suggest that lipoprotein PI levels may affect intravascular cholesterol transport.
Keywords: Chemistry, Biochemistry.